The Wars Within : Peoples and States in Conflict - Williams, Robin M., Jr., 1914-2006 (Book collections on Project MUSE., 2003)
"In The Wars Within, Robin M. Williams Jr. brings together decades of thought about ethnic conflicts in an effort to better understand their dynamics and to lessen their disastrous consequences. Williams presents a worldwide perspective, conscious that many studies of ethnicity focus primarily on the United States. The stakes of struggles can involve both material resources, such as oil, diamonds, and gold, and sociocultural goods, such as group status and cultural distinctiveness. Ethnic conflict, Williams finds, can be portrayed as a set of dynamic processes that may escalate from restrained confrontations over limited issues to devastating ethnic warfare and genocide."--Jacket